2008
DOI: 10.1212/01.wnl.0000286941.74372.cc
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotype and memory in the sixth decade of life

Abstract: Background-Virtually all adult studies of APOE genotypes and cognition have included individuals over 60. In older adults, ε4 carriers may manifest greater cognitive asymmetries than non-ε4 carriers even in the absence of overall mean differences. General cognitive ability may also be affected by aging and APOE genotype, but most studies have inadequately addressed this potential confound. The goals of this study were to examine, in middle age, the relationship of APOE genotype with episodic memory and verbal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 42 publications
4
56
3
Order By: Relevance
“…Overall, individual effect sizes ranged from -.25 to .64. Only one of the 26 studylevel effect sizes was reliably greater than zero (i.e., Schultz et al, 2008 Figure 2. Again, it can be seen that with increasing sample size, respective…”
Section: High and Low Executive Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, individual effect sizes ranged from -.25 to .64. Only one of the 26 studylevel effect sizes was reliably greater than zero (i.e., Schultz et al, 2008 Figure 2. Again, it can be seen that with increasing sample size, respective…”
Section: High and Low Executive Tasksmentioning
confidence: 99%
“…None of the study-level effect sizes for the high executive subgroup was reliably greater than zero. However, one of the effect sizes for the low executive tasks (i.e., Schultz et al, 2008) All of the foregoing analyses were rerun having excluded the fMRI studies as in such studies experimental groups usually are matched on several variables (e.g., cognitive performance) to disentangle neuronal differences (i.e. this is a less conservative approach of the present meta-analysis).…”
Section: High and Low Executive Tasksmentioning
confidence: 99%
“…Schultz et al (2008) compared the cognitive test performance of army cadets in the 6 th decade of life, to their scores on the same measure at age 20, and found ε4+…”
Section: Longitudinal Assessmentsmentioning
confidence: 99%
“…This led to the hypothesis that ε4+ may show cognitive advantages earlier in life, with performance advantages similarly being demonstrated in some (Alexander et al, 2007;Han et al, 2007;Schultz et al, 2008), although not all (Bunce et al, 2014;Bunce, Anstey, Burns, Christensen, & Easteal, 2011;Jorm et al, 2007) studies assessing genotype differences with neuropsychological batteries. Importantly, no steps have been taken to explore the potential moderating effects of early-life IQ and education on the trajectory of cognitive ageing in ε4+ through longitudinal research.…”
Section: Introductionmentioning
confidence: 99%
“…To date, reported effects of APOE e4 in mid-adulthood are inconsistent (for review; Lancaster et al, under review;Rusted & Carare, 2015;Salvato, 2015), with many studies reporting null effects. The exceptions are studies within the domain of memory, where detrimental effects are reported from the end of the fifth decade (Caselli et al, 2004;Jochemsen et al, 2012;Schultz et al, 2008). The inconsistency of reported findings is likely to stem from several methodological issues, including variation in age group included, control of potential moderators and sensitivity of cognitive tasks used.…”
Section: Introductionmentioning
confidence: 99%